Observations on possible use of the "Literate" game on poor readers in a multicultural classroom setting - Kalindi, Sylvia Chanda (2007)
The 'Literate' game, developed in Finland, is designed to help enhance learning lettersound correspondences and later reading of words with increasing complexity in children. The ̔Literate̓ game uses the phonetic/synthetic method of teaching phonological awareness which is currently seen as the basis of all reading. The ̔Literate̓ was piloted in Zambia (2005) to determine how it could be implemented into a multi-cultural setting. Factors such as pre-intervention skill and language background were examined in relation to observations of the game-based learning among the poor readers. A sample of 8 pupils (6 girls and 2 boys) was selected from a Grade 2 class at a private international school in Lusaka based on a screening test to identify poor readers. The pupils then underwent intervention on the 'Literate' game version which was specifically designed for the study and had a Zambian English accent in voicing of the game sounds. The players̓ performance during the intervention process was recorded by the computer and analyzed qualitatively. The results indicate that the reading performance of all the pupils improved pretty well both during and after the intervention even if it was noticed that pupils with better reading skills improved more than the pupils with poor skills. Furthermore, pupils with a language background different from one used in school also did not perform so well neither did they go so high in their levels on the 'Literate'. It was also observed that the 'Literate' game version used in this study had some deficits such as lack of clarity of the audio sounds which greatly affected the intervention process. It has therefore been concluded that the ‘Literate’ is a usable tool in literacy instruction and can also be used a multi-cultural classroom nevertheless issues of accent, sound quality and duration of intervention are important factors in the outcome of the intervention.